Association of Urinary Sodium Excretion with Vascular Damage: A Local Kidney Effect, Rather Than a Marker of Generalized Vascular Impairment. (16th December 2018) - Triantafyllou, Areti; Anyfanti, Panagiota; Gkaliagkousi, Eugenia; Zabulis, Xenophon; Vamvakis, Anastasios; Gkolias, Vasileios; Petidis, Konstantinos; Aslanidis, Spyros; Douma, Stella
Abstract : Evidence suggests that increased salt consumption induces blood pressure- (BP) mediated organ damage, yet it remains unclear whether it reflects a generalized micro- and macrovascular malfunction independent of BP. We studied 197 newly diagnosed and never-treated individuals with hypertension, intermediate hypertensive phenotypes, and normal BP, classified by use of 24-hour ambulatory BP monitoring. Sodium excretion and microalbuminuria were estimated in 24-hour urine samples, dermal capillary density was estimated from capillaroscopy, and arterial stiffness was estimated with pulse wave velocity (PWV) and augmentation index (AIx). Sodium excretion correlated with microalbuminuria ( p <0.001) and 24-hour and day- and nighttime systolic BP, but not with office blood pressure, arterial stiffness, or capillary density. In the multivariate analysis, the association with microalbuminuria was maintained ( p =0.007). In a population free from the long-standing effects of hypertension, increased salt intake appears to be associated with early signs of vascular kidney damage, rather than a diffuse micro- and macrovascular impairment.